2002
DOI: 10.1590/s1517-83822002000400006
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity of extracts of six macroalgae from the northeastern brazilian coast

Abstract: Hexane, chloroform and ethanol extracts of six marine macroalgae (Rhodophyta and Chlorophyta) from North Ceará coast (Northeast Brazil) were evaluated for antibacterial activity by the single disk method. Best results were shown by the hexane extracts of Amansia multifida against enteric Gram-negative strains such as Enterobacter aerogenes, Klebsiella pneumoniae, Pseudomonas aeruginosa, Salmonella typhi, S. choleraesuis, Serratia marcescens, Vibrio cholerae and the Gram-positive bacteria Bacillus subtilis and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
72
0
6

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(79 citation statements)
references
References 17 publications
1
72
0
6
Order By: Relevance
“…Soil streptomycetes are major producers of bioactive secondary metabolites [17][18][19][20]. It has been reported that organic solvents always provide a higher efficiency in extracting compounds for antimicrobial activities compared to water-based methods [21,22]. In our study, the antimicrobial products were extracted using ethyl acetate; the extract had different levels of activity against the tested Gram-positive, Gram-negative bacteria and C. albicans.…”
Section: Resultsmentioning
confidence: 86%
“…Soil streptomycetes are major producers of bioactive secondary metabolites [17][18][19][20]. It has been reported that organic solvents always provide a higher efficiency in extracting compounds for antimicrobial activities compared to water-based methods [21,22]. In our study, the antimicrobial products were extracted using ethyl acetate; the extract had different levels of activity against the tested Gram-positive, Gram-negative bacteria and C. albicans.…”
Section: Resultsmentioning
confidence: 86%
“…Uma vez que a P. aeruginosa é considerada um patógeno de grande importância em saúde pública e animal, e que vem desenvolvendo crescente resistência aos antimicrobianos, sendo, portanto, de difícil controle, os resultados do presente estudo denotam a importância da atividade antibacteriana do extrato da camomila frente a esta bactéria, já que diversos estudos relataram a resistência da mesma a diferentes extratos vegetais (Santos et al, 2011;Pelissari et al, 2010;Cordeiro et al, 2006;Andrade et al, 2005;Vasconcelos et al, 2004;Lima-Filho et al, 2002). Tal fato reforça a hipótese de que o extrato da camomila pode ter potencial para fornecer substâncias com atividade antibacteriana in vitro.…”
Section: Resultado E Discussãounclassified
“…Organic solvents were more efficient in extracting compounds with high antifungal potential compared to water based methods [33]. According to our experiments, S. vulgare petroleum ether extract, tested at 100 mg/mL, displayed an important antifungal activity leading to more than 43% pathogen inhibition for those extracted from samples collected from Tunis, Mahdia2 and Monastir.…”
Section: Discussionmentioning
confidence: 73%
“…Numerous studies have also demonstrated the effectiveness of organic extracts in extracting secondary metabolites with antifungal activities against various soil borne plant pathogens compared to water-based procedures [24,33]. In fact, Pérez et al [43] reported that the yield of extractable antimicrobials from the different seaweed species is solvent-dependent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation